Improve Understanding of English by Using Music for Elementary School Students - Windha Yunanti (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
The purpose of this article is to discuss about how to improve students' understanding ofEnglish using music. The method used in data collection is a journal review. Variousmedia and methods can be used to improve students' understanding of English and oneof them is music. Music is one of the media that is useful for developing children'sunderstanding of the English language. Different types of music can be used. By usingmusic students can easily understand and understand English.